O diabo veste Prada: o fazer da moda no corpo vestido como vitrina de identidades - Freire, Cristina Gomes (2010)
This research enquiries how fashion takes place constructing people`s identities, starting on an analysis of the film The Devil Wears Prada, from David Frankel. Throughout sociossemiotics and the interaction and sense regimes concept by Landowski, we study the actor`s construction on their social interactions in a the plot focused on the fashion industry scenario in which the identity paths are inserted. We describe and analyze on a sequence of small filmic narratives the way fashion takes place as cognitive modalizer of the human beings nowadays; the way it is a bush of sensitive interactancial relations; the way it works as regulatory of the ways of dressing in the social scenery and also how fashion makes accidents possible. We investigate the ways of articulation between body and clothes emphasizing that those kinds of arrangements create innumerous possibilities of appearances and how they interfere on the subjetal dynamics. We pointed as hypothesis that the style and the way it structures itself by the means of the outfits and the taste for fashion brings up forms of behavior and life actualized on the presence ways. Another hypothesis thrown was that fashion and, in its consequence, its byproducts such as clothes, accessories and the garment arrangements take place into the edification of the making to be of the individuals. Besides, we could see, in conclusion, that the presence ways of the persons are governed by the visibility ways, which create simulacral figures programmed and manipulated by the fashion industry. The ways of presence and the ways of visibility product figures broadcasted on the media, which are figurative marks of the style for the subjective searches of escape from the modulations by the adjustments and accident mechanism. We studied these mechanisms in order to understand how, on its reiteration, the styles are brought together that segment and identify belonging groups of the social constitution. The research bounds to the communication area as we take fashion as a communicational phenomenon that broadcast identities and style due to the persons make their bodies boards for the dressing that communicate messages which meanings are apprehended by the visual aesthetics